Inhibition of endotoxin‐induced perinatal asthma protection by pollutants in an experimental mouse model. Issue 4 (15th February 2013) - Reiprich, M.; Rudzok, S.; Schütze, N.; Simon, J. C.; Lehmann, I.; Trump, S.; Polte, T.; Simon, Hans‐Uwe
Abstract Background One of the most promising strategies to face the increasing asthma prevalence and to prevent disease development might be an early contact with microbial compounds. However, little is known about an interaction between an early‐life contact to microbial compounds leading to asthma protection in the offspring and a co‐exposure to allergy‐promoting pollutants. Methods Pregnant BALB/c mice were repeatedly exposed to aerosolized endotoxin (lipopolysaccharide, LPS). The offspring was further exposed to aerosolized LPS before allergen sensitization with ovalbumin (OVA). Some of the mice were co‐exposed to mycotoxins or diesel exhaust particles (DEP) during pregnancy. The 6‐week‐old offspring was immunized with OVA and analyzed in a murine asthma model. Results While the offspring of naïve mothers developed an asthma‐like phenotype, the offspring of mice perinatally exposed to LPS was significantly protected. Co‐exposure of mice to mycotoxins or DEP during pregnancy inhibited the LPS‐induced protection leading to the development of eosinophilic airway inflammation, airway hyperactivity, and increased antigen‐specific IgE levels in the offspring. Furthermore, the asthma‐preventive effect of perinatal LPS exposure was IFN‐gamma dependent. Additionally, the IFN‐gamma promoter of CD4+ T cells in the LPS‐exposed offspring revealed a significant protection against loss of histone 4 acetylation, which was abolished after prenatal co‐exposure to pollutants. Prenatal treatment of mice with the antioxidant N‐acetylcysteine reversed the pollutant‐induced increased asthma risk in the offspring. Conclusion Our results show that exposure to pollutants during pregnancy may cause the development of allergic asthma in the offspring by inhibiting the endotoxin‐induced perinatal asthma protection.